Prevalence of nasal septum deviation using cone-beam computed tomography: A cross-sectional study - Mahkameh Moshfeghi; Bahareh Abedian; Mitra Ghazizadeh Ahsaie; Farzam Tajdini (Wolters Kluwer Medknow Publications, 2020)
Background and Aim: Nasal septum deviation (NSD) increases the chance of nasal obstruction, sinusitis, and upper airway and middle ear infections and can affect vocal cord activity, beauty, and breathing. The present study investigated the prevalence of NSD and its relation to gender, age, and history of trauma using cone-beam computed tomography (CBCT). Subjects and Methods: This cross-sectional study was performed on the data from CBCT examinations of 386 patients referred to two oral and maxillofacial radiology centers in Tehran, Iran, from January 2016 to January 2017. The presence of NSD and its type according to the Mladina's classification were evaluated. The effect of age, gender, and history of trauma on the prevalence of NSD was considered using a logistic regression. Results: 86.6% (confidence interval = 0.81, 0.91) of the patients showed NSD. The prevalence was 19.4% type 1, 6.2% type 2, 20.7% type 3, 5.4% type 4, 4.4% type 5, 0.3% type 6, and 30.3% with type 7. The logistic regression indicated that the chance of deviation of nasal septum increased with age and every 10-year increase in age increased the odds of septal deviation by 0.32 (P < 0.001 and odds ratio = 1.032). Gender (P = 0.094) and history of trauma (P = 0.79) had no effects on the chance of deviation of nasal septum. Conclusion: This study showed that the frequency of NSD was 86.6%, with type 7 being the most common type, followed by type 3 and 1. NSD showed no association with trauma and gender, and the increase in age increases the chance of NSD.